A long-term stable organic semiconductor photocathode-based photoelectrochemical module system for hydrogen production. Issue 25 (27th May 2022) - Seo, Sehun; Lee, Jong-Hoon; Kim, Yejoon; Kim, Seungkyu; Yoon, Chang Jae; Choi, Hojoong; Lee, Sanseong; Lee, Kwanghee; Kim, Heejoo; Lee, Sanghan
Abstract : This work provides new insight into photoelectrochemical hydrogen production under real sunlight by developing a photoelectrochemical module system based on an organic semiconductor photoelectrode with a maximized performance by metal encapsulation. Abstract : Photoelectrochemical (PEC) water splitting based on organic semiconductors (OSs) is a promising way to enable sustainable hydrogen production because of their high photovoltaic performance and mass productivity by low-cost printing. However, their application to photocathodes has drawbacks such as low efficiency and poor operational stability, which result from rapid device degradation or failure under harsh operating conditions. In this study, we developed a stable and efficient OS-based PEC photocathode module using the metal encapsulation technique. Our OS-photocathode shows a photocurrent density of −12.3 mA cm −2 at 0 V versus the reversible hydrogen electrode (RHE) and an onset potential of 1 VRHE . These are similar to the values of both the short circuit current and open circuit potential of its photovoltaic cell. Notably, our photocathode represents unprecedented stability: maintaining over 95.4% of the maximum photocurrent for over 30 h without significant degradation of the OS. In addition, we successfully demonstrate a PEC module based on OS-photocathodes in parallel connection in a real environment, confirming the potential of the OS-based photoelectrodes for sustainable hydrogen production.